The Application of Technology in the Age of Covid-19 and Its Effects on Performance - Abu Muna Almaududi Ausat (CV. Media Digital Publikasi Indonesia, 2023)
The Covid-19 pandemic has harmed many parties, but that is not the only reason. Individuals and organizations must be adaptable to changing conditions. One of them is to adapt more to technological advances to have a positive effect on the long-term sustainability of performance, both on an individual and organizational level. In this study, the author will describe the use of technology during the Covid-19 pandemic, as well as how it relates to performance, using a descriptive qualitative approach method. The findings of this study show that technology is an excellent tool for overcoming adversity and becoming a solution for surviving and competing in the age of disruption, particularly during a crisis. We must be adaptable as thinking individuals and organizations to improvise with technological sophistication. Because one of the primary goals of technology is to aid in the improvement of the economy. The study's limitation is that it still does not focus on a specific unit of analysis, which is what type of technology is meant. As a result, it is recommended that future research focus on the type of technology discussed by using a quantitative approach method on specific objects with a large number of samples, and that interview techniques be used as a supplement to data collection techniques. This study can also be used as a reference source to supplement references demonstrating the importance of technology during the Covid-19 pandemic.